Application of Bacterial Foraging Algorithm in The Allocation of DSTATCOM in 50-bus Canteen Feeder (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Voltage instability has been identified as the most critical factor responsible for poor power quality in electric power systems. The high losses experienced at the distribution level of these systems has become a major concern to power system operators, with about 10-13% of the total generation being dissipated as heat. Maintaining the system voltage within an acceptable limit will go a long way in reducing these losses and enhancing the overall system operational capability. The objective of this paper is to improve the voltage magnitude and reduce overall power losses in an existing 50-bus radial distribution feeder via the allocation of Distribution Static Compensator (DSTATCOM) using an established bacterial foraging algorithm (BFA) based model. The application of the swarm-based meta-heuristic model is extended to a three-quarter (75%) loading condition of the standard IEEE 33-bus test network and then, employed on the 50-bus Canteen feeder for both normal (100%) and three-quarter (75%) loading conditions. Comprehensive analysis was performed for both networks and the results were compared with their respective base-case scenarios. The final results of the evaluation obtained through simulation showed appreciable reduction in power losses and improvement in overall voltage profile with the allocation of DSTATCOM in both networks using the BFA based model. Voltage improvement in the region of 20.04% and active power loss reduction of 24.86% were recorded for three-quarter loading of the IEEE test network. For the 50-bus Canteen feeder, an overall voltage profile improvement of 6.13% and active power loss reduction of 22.84% were achieved for normal loading condition, whereas 2.99% and 19.71% improvement in total voltage profile and active power loss respectively were attained under three-quarter loading condition.
Keywords: Distribution Static Compensator; Bacterial Foraging Algorithm; Loss Minimization; Voltage Profile; Canteen Feeder.